Soil-transmitted helminthiasis among adolescents in Anaocha Local Government Area, Anambra State, Nigeria: Insights and recommendations for effective control. - Ogechukwu B Aribodor; Eunice C Jacob; Nwadiuto O Azugo; Uche C Ngenegbo; Ifeanyi Obika; Emmanuel M Obikwelu; Obiageli J Nebe (PLoS ONE)
Over the past decade, Anambra State, Nigeria, has implemented mass administration of medicines (MAMs) to combat soil-transmitted helminthiasis (STH), a significant public health challenge in low-income regions. Nevertheless, these efforts have predominantly focused on pre-school and school-aged children, leaving a notable gap in understanding STH infection rates and the efficacy of these campaigns among secondary school adolescents, who have been excluded from this initiative. Our study aimed to address this critical knowledge gap by assessing soil-transmitted helminthiasis (STH) prevalence and contextual factors hindering effective control among adolescents in Anambra State, Nigeria. We actively engaged 443 adolescents with a mean age of 14 years in a school-based cross-sectional study in selected communities within the Anaocha Local Government Area from 8 February to 7 July 2023 following informed consent and assent procedures. Employing a stratified random sampling technique, we collected demographic data and assessed STH risk factors using a structured questionnaire hosted on the Kobo Toolbox platform. For quantitative analysis of STH infections, the Kato-Katz technique was used. Analysis was performed using SPSS version 25, incorporating descriptive statistics and multinomial logistic regression, with statistical significance set at p<0.05. Of the 443 (213 males (48.0%) and 230 females (52.0%) adolescents studied, the overall prevalence of STH observed was 35.2% (156/443). Ascaris lumbricoides was the prevalent STH species (16.9%), followed by Trichuris trichiura (1.4%) and hookworm (0.5%). Only light-intensity infection was observed. Mixed infections were observed in 16.5% of adolescents, involving A. lumbricoides and hookworm (10.8%), followed by A. lumbricoides and T. trichiura (3.2%) and all three STH (2.5%). The observed overall prevalence was not statistically significant with respect to gender (OR: 0.961; 95% CI: 0.651-1.420; p > 0.05) or age (OR: 0.686; 95% CI: 0.459-1.025; p>0.05). Class (grade level) (OR = 1.75, 95% CI: 1.25-2.45, p = 0.003), knowledge and transmission of STH infection (OR = 0.60, 95% CI: 0.42-0.86, p = 0.008), parental occupation (OR = 1.90, 95% CI: 1.35-2.67, p < 0.001), parents' literacy level (OR = 0.68, 95% CI: 0.48-0.96, p = 0.027), and the type of toilet (OR = 2.15, 95% CI: 1.54-3.00, p < 0.001) were all significantly correlated with STH infection. These findings highlight the role of adolescents in sustaining soil-transmitted helminthiasis (STH) transmission. Coupled with school-based deworming expansion, innovative improvements in water, sanitation, hygiene, and awareness can provide a cost-effective, sustainable solution for combatting STH infections in Anambra State.